A multiscale model for the prediction of ballistic performance of fiber-reinforced composites. (August 2021) - Zhu, Wenqing; Liu, Junjie; Wei, Xiaoding
Highlights: A general linear relationship between the optimal dimensionless matrix viscosity and the dimensionless impulse duration time is found. A multiscale model to predict the ballistic limit of fiber laminates is developed and applied to explain how the matrix properties affect the impact performance. Abstract: This study investigates in-depth the effects of dimensions and properties of constituents at microscale on the impact performance of macroscopic fiber-reinforced laminates. A numerical algorithm incorporating the dynamic shear-lag model is developed. Applying the numerical dynamic shear-lag model to three typical impulse forms, a common linear relationship between the optimal dimensionless viscosity and impulse duration emerges. This linear relationship can guide the selection of matrix materials to optimize the energy dissipation. Furthermore, a new multiscale model is established by extending the dynamic shear-lag model to the laminate scale to take into account the contribution to the energy absorption from the matrix. This multiscale model successfully captures the effect of matrix properties on the ballistic limits of aramid fiber and carbon fiber composites from previous experiments by two independent groups.